Comparative analysis of Thai indigenous rice on growth, yield, and leaf nutrient under salinity conditions - Khomphet, Thanet; Zhao, Yong (Frontiers in Agronomy, 2025)
Salinity is one of the most detrimental environmental stresses, significantly reducing rice yield and quality. Salinity tolerant varieties are crucial for rice production in Southern Thailand. The objectives of this study were: 1) to examine the response on growth, yield, and leaf nutrient composition of 10 indigenous rice varieties from Nakhon Si Thammarat Province under salinity conditions, and 2) to identify varieties capable of surviving and producing yield under saline conditions. The experiment was designed as a factorial arrangement in a completely randomized design with two factors. The first factor was the salinity level of irrigation water, consisting of 0.0%, 0.4%, and 0.8% salinity. The second factor was the indigenous rice varieties, which included Dok Kha, Hom Bon, Dawk Pa-yawm, Luk Lai, Leb Nok, Leuang, Banpeang, Chorlumpee, Sang Yot (Tha Sala), and Sang Yot (Bang Khan). Significant differences were observed across salinity levels and among rice varieties for most traits. All rice varieties experienced substantial reductions in growth when exposed to higher salinity levels. The principal component analysis revealed that rice varieties exhibited varying responses in agronomic traits, yield traits, and leaf nutrients under different salinity conditions. Based on their ability to survive in saline environments and yield production, Luk Lai, Leb Nok, and Sang Yot (Bang Khan) are recommended for farmers for future production on saline soils.